Investigating the Relationship on CO2, Energy Consumption and Economic Growth: A Panel Data Approach - Nordin, Sayed Kushairi Bin Sayed; Sek, Siok Kun (Journal of Reviews on Global Economics, 2019)
In this study, empirical analysis is conducted to reveal the relationship between three variables: energy consumption, GDP and CO2. The analysis is based on 13 oil importing countries and 11 oil exporting countries. The main objectives are (1) to reveal the long-run relationship based on three different models using second generation panel unit-root and panel cointegration tests and (2) to investigate the short-run relationship between pairs of variables using VAR Granger causalityÂ test. The panel unit root tests indicate that each variable is integrated of order one, I(1). Based on cointegration tests, the results reveal a long-run relationship in one of the models in both countries. The VAR Granger Causality shows evidence of a short-run relationship between the variables in both groups of countries.